Kaizen for Europe : - Hannam, R. G. (Information press, 1993)
Kaizen means continous improvement and it is one of the many strategic Japanese manufacturing and management methods discussed in this book. The strategies are presented and explained in terns of their Japanese implementation, and then it is shown how they can be transferred to the West.